Automated Quantification of Blood Loss Compared to Qualitative Estimation in 300 Vaginal Deliveries [20J]. (May 2018) - Rubenstein, Andrew; Zamudio, Stacy; Al-Kahn, Abdulla; Douglas, Claudia; Sledge, Sharon; Thurer, Robert
Abstract : INTRODUCTION: Under estimation of blood loss and delayed diagnosis of obstetric hemorrhage are leading causes of maternal morbidity and mortality. Failure to visually recognize significant hemorrhage early is often responsible. Accurate quantification of blood loss during delivery is therefore recommended to facilitate rapid recognition and implementation of hemorrhage protocols and improve outcomes. METHODS: We assessed quantified blood loss (QBL) using an automated system (Triton L&D™, Gauss Surgical, Los Altos, CA) compared to the attending physician's clinical estimates during 300 vaginal deliveries. The system batch weighs all blood containing sponges, towels, pads and other supplies and automatically subtracts their dry weights. It also facilitates measurement of blood collected in the under-buttocks drape and subtracts the measured amount of amniotic fluid. Each method was performed independently and clinicians were blinded to the device's results. RESULTS: Mean QBL (405.8 ± 275.2 ml) was significantly greater than visually estimated blood loss (304.9 ± 135.2 ml) (P<.0001). Critically, QBL detected hemorrhage (blood loss > 500 ml) in 27.7% of patients compared to 5.1% of patients using visual estimation (P<.0001). Visual estimation of ≥1, 000 ml was recorded in only 1 patient, whereas 13 patients (4.3%) had a blood loss > 1, 000 ml by QBL (P<.0001). CONCLUSION: Our data demonstrate that QBL facilitated by an automated system recognizes more patients with excessive blood loss than visual estimation. The value of QBL as a public health safety initiative requires clinicians to accept the long-known inadequacy of qualitative estimation. Further studies of clinical outcomes related to implementation of QBL are needed.